Investigating Subjective Well-being. A Quantitative Study on Special Education Teachers’ Life Satisfaction. - Ianniello , Annalisa; Corona , Felice (Advances in Social Sciences Research Journal, 2023)
Teachers are the architects of society [1]. A teacher who is satisfied with her life plays a vital role in the elevation of equal and inclusive societies. This study aims to determine the life satisfaction perceptions of special education teachers in Italy. The study was conducted with a sample of 394 teachers from Campania, belonging to all school levels. (Preschool, Primary, Lower Secondary and Upper Secondary school). In this study the descriptive survey model was used. To collect the data, the Satisfaction with Life Scale developed by Diener, Emmons, Larsen & Griffin (1985) [2], administered in the already validated Italian version [3], was used. The data were analysed with the SPSS program following the scoring indications of the instrument. The results show that most of the interviewees fall into the brackets expressing satisfaction (from very satisfied to averagely satisfied), while only 37 teachers (equal to 9% of the total) were below the average bracket.